Perancangan dan Pembuatan JIG FOG Lamp Mobil Dengan Material Aluminium - Rizki Aulia Nanda; Karyadi Karyadi; Fathan Mubina Dewadi; Muhammad Nuzan Rizki (Jurnal Mekanik Terapan, 2023)
Car Fog Lamp is a safety feature whose function makes it easier for the driver to keep shining in bad weather conditions. Fog Lamp itself is a weather lamp that is produced to penetrate fog and illuminate the road ahead, with this need, the company developed a jig for fog lights on cars, Jig is basically a tool used in the machining process to make more accurate copies of production parts. The purpose of this research is to make a small industrial-scale jig for car fog lamps. The method used to make the jig starts with determining the size of the fog lamp, the design process, design input to the CNC, running CNC, and jig results. The results of this study began by displaying the design results with dimensions of 396 x 140 x 45 (p x l x h (mm)) with a hole diameter of 75 mm at a depth of 40 mm. The test was carried out using 10 specimens with successful results according to design 7 and failure 3. Then the success rate for making car jigs is 70%. Failure in the manufacture of jigs, namely defects in the results of CNC milling and oval shape due to fatigue in the tool.